2019
DOI: 10.18632/aging.102041
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidins ameliorate neuronal oxidative damage by inhibiting GSK-3β-dependent mitochondrial permeability transition pore opening in an experimental model of sporadic Alzheimer’s disease

Abstract: Mitochondria-associated oxidative stress plays a crucial role in Alzheimer’s disease (AD). Grape seed proanthocyanidins (GSPs) have been reported to prevent oxidative stress. In this study, we investigated the underlying mechanisms of GSPs in protecting neurons against oxidative injury in an experimental model of sporadic AD. Primary mouse cortical neurons were subjected to streptozotocin (STZ) to mimic neuronal oxidative damage in vitro , and mice were subjected to intracerebroventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Similar effects of SA have been reported, where its derivative sinapine restored the levels of acetylcholine and improved learning and memory [20,23,59]. Furthermore, studies have revealed that ICV-STZ administration has been associated with neuronal loss in the CA1 region of the hippocampus [60][61][62]. We found that apart from improvements in behavioral parameters, oxidative stress, anti-inflammatory cytokines and hippocampal ChAT expression, SA treatment was accompanied by attenuation of STZ-induced neuronal loss in the CA1 region of the hippocampus.…”
Section: Discussionsupporting
confidence: 69%
“…Similar effects of SA have been reported, where its derivative sinapine restored the levels of acetylcholine and improved learning and memory [20,23,59]. Furthermore, studies have revealed that ICV-STZ administration has been associated with neuronal loss in the CA1 region of the hippocampus [60][61][62]. We found that apart from improvements in behavioral parameters, oxidative stress, anti-inflammatory cytokines and hippocampal ChAT expression, SA treatment was accompanied by attenuation of STZ-induced neuronal loss in the CA1 region of the hippocampus.…”
Section: Discussionsupporting
confidence: 69%
“…Proanthocyanidins (PAC) are a group of antioxidant polyphenolic flavonoids present in the dark pigmented fruits and vegetables [ 35 ]. Rodríguez-Pérez et al reported that PAC prevent the H 2 O 2 -induced mitochondrial dysfunction and apoptosis in embryonic kidney cells [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of GSP with intestinal microbiota converts dietary polyphenols into two phenolic acids, 3-hydroxybenzoic acid and 3-(3-hydroxyphenyl) propionic acid, in the brain. There is an evidence that both these phenolic acids interfere with the generation of the neurotoxic Abeta peptides involved in AD pathogenesis [38,94].…”
Section: Anthocyanin Absorption Bioavailability and Metabolismmentioning
confidence: 99%
“…The type of ANT and its concentration depends on the variety and cultivation season. Peonidin, delphinidin, and malvidin are major ANTs in grapes [94,99].…”
Section: Alzheimer’s Disease and Anthocyaninsmentioning
confidence: 99%